Introduction of Forage Feed Processing Technology for Cows in the Damang Saiyo Farmer Group - Amir, Yurni Sari; Zelpina, Engki; Lefiana, Delli; Noor, Prima Silvia; Sujatmiko, Sujatmiko; Siregar, Ramond; Lutfi, Ulva Mohtar; Syamil, Muhammad; Rahim, Alhafid Septia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Damang Saiyo Farmer Group is one of the farmer groups located in Batu Balang Village, Harau District, Lima Puluh Kota Regency. This group is quite active, especially in the agricultural sector. Most of the group members are active in agriculture, such as planting rice and gardening. However, there are also group members who raise livestock such as cows. Raising cattle for group members is a side activity and as family savings. Supporting natural resources such as empty land, fertile soil and easy access to green fodder in the form of grass and agricultural waste are supporting factors for raising cattle. The problems found in the Damang Saiyo Farmer Group are the lack of community knowledge about green fodder and never having processed green fodder from agricultural waste such as straw. So far, straw has not been optimally utilized as cattle feed.